A User-friendly Tool for Modeling and Simulation of Discrete Event Dynamic Systems - Ibl, Martin (Wolters Kluwer ČR, a. s., 2016)
Currently, there are a number of tools for modelling and simulation of discrete event dynamic systems. One of the most widespread tools are Petri nets, which allow in addition to verify a number of assumptions that are placed on the model (e.g. liveness, boundedness, etc.). In terms of user-friendliness, one of the main drawbacks of Petri nets tools is their primary purpose as the support of science and research. In this work is implemented the editor of Petri nets, which will be primarily designed to support teaching (classical and distant forms). The main differences from the classic tools are clarity and clearness for all phases of the life cycle of the with the tool. User-friendliness is about convenience and customization options in the course of the modelling, clearness including animation of the dynamics in the course of the simulation and unification and simplicity of the results of the simulation or verification.
Uživatelsky přívětivý nástroj pro modelování a simulaci diskrétních dynamických systémů řízenými událostmi
Keywords: Modelling; Simulation; Animation; User-Friendliness; Petri Nets; modelování; simulace; animace; uživatelská přívětivost; Petriho sítě